The Influence of the Storytelling Method on the Speaking Ability of Children Aged 5-6 Years in Kindergarten St-Antonius 1 Medan - Tri Novantri; Aman Simaremare; Anita Yus; Gita Noveri Eza; Srinahyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the presence or absence of the influence of the storytelling method on the ability to speak children aged 5-6 years in TK ST-Antonius 1 Medan. This research was conducted at the St-Antonius 1 Medan TK which is located at Jalan HM Joni No. 52 A Medan. The population in this study was all children in TK ST-Antonius 1 Medan with a total of 103 children. The research design used is pretest-post-test design. Sampling techniques, namely with Purposive Sampling techniques in class B3 as many as 28 children. The data obtained were analyzed using non -parametric statistics Wilcoxon signs rank test. The results of the analysis obtained the average class value using a conventional storytelling method of 16.21 with SD = 3.26 and the average class value with an interactive storytelling method of 25.78. With SD = 2.10. From the hypothesis calculation data obtained asymp. Sig. (2-tailed) worth 0,000. smaller than 0.05 (<0.05), it can be concluded that there is a significant effect of the interactive storytelling method on the ability to speak in children aged 5-6 years in kindergarten. St. Antonius 1 Medan compared to the ability to speak children taught by conventional storytelling methods.